2018
DOI: 10.29312/remexca.v4i2.1231
|View full text |Cite
|
Sign up to set email alerts
|

Determinación de las tasas de ventilación natural en un invernadero mediante modelos teóricos y gases trazadores

Abstract: La mayoría de los invernaderos en México utilizan ventilación natural como mecanismo principal de controlar el clima. La cuantificación de las tasas de ventilación es difícil porque éstas dependen del efecto de la f luctuación de viento, resistencia de las ventanas al paso del aire y geometría del invernadero en el campo de presiones del viento sobre la estructura. El objetivo del presente trabajo fue determinar las tasas de ventilación natural de un invernadero, bajo tres config… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…These results reaffirm some conclusions already determined in previous works related to the natural ventilation of greenhouses, where it was identified that the renewal indexes are dependent on the ventilation configuration used [68][69][70][71]. It was also identified that there is a linear relationship between the renewal index and wind speed [38,56,72,73], the ventilation configuration that allows to obtain the highest renewal index values is the combined configuration of roof and side vents [10,16,74,75].…”
Section: Renewal Index (Ri)supporting
confidence: 89%
“…These results reaffirm some conclusions already determined in previous works related to the natural ventilation of greenhouses, where it was identified that the renewal indexes are dependent on the ventilation configuration used [68][69][70][71]. It was also identified that there is a linear relationship between the renewal index and wind speed [38,56,72,73], the ventilation configuration that allows to obtain the highest renewal index values is the combined configuration of roof and side vents [10,16,74,75].…”
Section: Renewal Index (Ri)supporting
confidence: 89%
“…It is also observed that the fixed vents in the roof region for this case function as air inlet areas over a region approximately in the lower 3/4 of the longitudinal section and an air outlet area approximately over the upper 1/4 of the longitudinal section in all the spans. This may indicate that the longitudinal slope generates on the fixed windows of the greenhouse roof regions positive pressure for the air inlet zones and negative pressure for the window section where there is an air outlet flow [52,53].…”
Section: Qualitative and Quantitative Characteristics Of Airflow Patternsmentioning
confidence: 99%
“…Natural ventilation is the most important phenomenon to be controlled inside a protected agricultural structure, since it facilitates the exchange of mass and energy between the crop plants, the surrounding air inside the structure, and the external environment [15]. Therefore, in a structure that relies on natural ventilation as a method of climate control, it is necessary to ensure an adequate and uniform movement of air flow, which will guarantee that the microclimatic variables will remain within optimal levels for plant growth and development [16].…”
Section: Introductionmentioning
confidence: 99%
“…Four decades later, some researchers have proposed the use of Bernoulli's equation as a calculation method to estimate the amount of air that can circulate through a ventilation area, thus generating the basic theory of natural ventilation in greenhouses [26][27][28]. Similar methodologies were also proposed for other types of structures such, as screenhouses [16]. Currently, there are already calculation techniques that help to understand the behavior of natural ventilation, among these are: (i) mass balance with a tracer gas, (ii) indirect energy and mass balance methods, (iii) direct measurements of velocities and pressures at windows, (iv) visual methods on scale models, and (v) wind tunnel studies [17,29].…”
Section: Introductionmentioning
confidence: 99%